The effects of Covid-19 on the performance of the shares of B3´s sectors - Caldas, Antonio Vinicius Silva; Silva, Emerson de Sousa; Silva Junior, Antonio Francisco de Almeida; Cruz, Ulysses de Brito (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This work has aimed at verifying the behavior of the productive sectors of B3 during the Covid-19 pandemic, considering the period from January 2nd to May 12th, 2020. This descriptive and quantitative research has analyzed the average monthly return and the traded quatities of 55 sectors. The techniques used in the data analysis were: cluster analysis, difference in differences, and the tests of randomness, normality, and serial correlation. It was concluded that Covid-19 affected the groups differently, one of which behaved as a market with weak efficiency. The study contributes as an empirical finding that the sectors that makeup B3 showed different behaviors in the face of the pandemic in the new coronavirus.